2006
DOI: 10.1175/mwr3134.1
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between SAR-Derived Wind Vectors and Wind at 10-m Height Represented by a Mesoscale Model

Abstract: Wind vectors over the ocean were extracted from a large number of synthetic aperture radar (SAR) images from the European Remote Sensing Satellites (ERS-1 and ERS-2). The wind directions are inferred from the orientation of wind streaks that are imaged by the SAR, while the wind speeds are retrieved by inversion of the C-band model CMOD4. The derived wind directions and speeds were compared to wind vectors from the numerical Regional Model (REMO) that are available hourly on a 55-km grid. The large number of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(44 citation statements)
references
References 21 publications
1
43
0
Order By: Relevance
“…The REMO physics are adapted from the ECHAM4 global model of the Max-Planck-Institute for Meteorology (Koch and Feser, 2006). The specific REMO simulation used here was performed with nudging of large scale meteorological fields (von Storch et al, 2000) to keep the simulated state close to the driving state at larger scales, while allowing the model to freely generate regional-scale weather within Europe (Feser and Weisse, 2001).…”
Section: Biogeosciencesmentioning
confidence: 99%
“…The REMO physics are adapted from the ECHAM4 global model of the Max-Planck-Institute for Meteorology (Koch and Feser, 2006). The specific REMO simulation used here was performed with nudging of large scale meteorological fields (von Storch et al, 2000) to keep the simulated state close to the driving state at larger scales, while allowing the model to freely generate regional-scale weather within Europe (Feser and Weisse, 2001).…”
Section: Biogeosciencesmentioning
confidence: 99%
“…The prognostic variables are surface air pressure, temperature, horizontal wind components, specific humidity and cloud water. The physics scheme applied is a version of the global model ECHAM4 physics of the Max-Planck-Institute for meteorology adapted for the regional model (Koch and Feser, 2006). The model simulation was computed with additional "nudging of large scales" (von Storch et al, 2000).…”
Section: Model Inputsmentioning
confidence: 99%
“…temperature Precipitation radiation humidity Cosby et al (1984), Saxton et al (1986) Temperature (max,min, daily average) REMO Feser et al (2001), Koch and Feser (2006), REMO Jacob and Podzun (1997), Kalnay et al (1997) examine the changes in terrestrial CO 2 exchange. This simple division to compare model output is arbitrary and does not follows ecosystem or bioclimatic zones boundaries.…”
Section: Modelmentioning
confidence: 99%
“…The hourly ground-level wind speed and surface air pressure fields cover Europe and the North Atlantic with 0.58 3 0.58 resolution (around 50-60 km). Koch and Feser (2006) compared satellite-retrieved wind data with surface winds simulated in REMO and found that REMO describes wind speeds realistically. Weisse et al (2005) show that surface wind fields and their statistics are homogeneous and reasonably well simulated over the sea in coastDat.…”
Section: Introductionmentioning
confidence: 99%